EFFICACY AND TOLERABILITY OF ORAL IRON CHELATOR, DEFERASIROX - Tahir, Awais; Syed Ibrar Hussain,; Huma Saleem Khan,; Sumaira Khalil,; Syed Zulfiqar Haider,; Munir Akmal Lodhi, (Journal of Ayub Medical College Abbottabad, 2021)
Background: Thalassemia major is the severe form of Î² thalassemia characterized by severe anaemia, hepatosplenomegaly and facioskeletal changes due to increased haemolysis of defective red blood cells. In iron overload states, high levels of iron exceed the iron-carrying capacity of transferrin within the plasma, leading to the formation of nontransferrin-bound iron form. These nontransferrin-bound iron forms can be taken up into cells, including liver, heart, and endocrine cells leading to organ damage. To prevent complications associated with hemosiderosis, iron chelation therapy remains one of the main objectives of clinical management of the patients affected by Thalassemia Major. Methods: Thirty-seven patients were enrolled using non randomized convenience sampling technique after the written consent from patients. Patients age 2-30 years were enrolled in this study. Serum Ferritin, ALT, Serum Creatinine were checked at the start of the study, 3 months, 6months and then at the end of the study, i.e., at 9 months of the commencement of the study. They were also assessed for other side effects pertaining to oral tolerability of the drug like vomiting, nausea, GI upset, diarrhoea, urinary complaints or any other subjective complaint. Results: Of the 37 patients, 20 were male (54.1%) and 17 were female (45.9%). Mean age of the patients was 10.2 years (Min. 3 years, Max 21 years). The average serum Ferritin at baseline was noted as 3440 which increased after a period of 3 months, 6 months and 9 months with average of 3359, 3677 and 4394 respectively. After the period of 9 months largest 95% confidence interval of serum Ferritin levels was observed in the range of 3420.17 to 5368.63. In our study, 17 patients required alternative chelation (46%). These patients needed IV Deferioxamine because of the rising trend of Serum Ferritin after the study. Conclusion: From the results of our study, we infer that oral Deferasirox is not an effective iron chelator. If the patients are taking oral deferasirox, their Serum Ferritin should be checked 3 monthlies. The drug is effective only in maintaining Serum Ferritin levels with levels less than 1500ng/ml. Intravenous Deferioxamine still should be preferred over oral iron chelators for effective control of iron overload and its complications.